Global burden of trichiasis in women as compared to men: Findings from the Global Trachoma Mapping Project - Moyo, George (Department of Surgery, 2020)
The secondary analysis undertaken for this MPH dissertation examines the global prevalence of trichiasis in relation to gender in trachoma endemic countries. Part A is the research protocol which outlines the background and the process of this research. This study is a population-based analytical study using data from the Global Trachoma Mapping Project (GTMP). GTMP was a standardized population-based trachoma prevalence survey undertaken to provide trachoma prevalence estimates. GTMP data was collected using the World Health Organisation–recommended population based prevalence survey methodology. Trachoma suspect district were identified for inclusion and multistage random sampling was used to sample households for examination of residents for clinical trachoma. Part B presents the background and highlights the importance of this research by exploring the existing theoretical and empirical literature relevant to the topic. It describes how trachoma is transmitted, its clinical manifestations, and the way it can lead to blindness. Results from previous studies on gender and trichiasis are presented. Part C presents the research project in a format suitable for journal submission. The background of this research project is summarized and the meta-analysis is conducted at the global level, at the country level, the regional level, the state level and at the EU level but all in accordance to prevalence of trichiasis in the EUs. The implications of the findings are discussed and limitations in interpretation presented.